Enhanced Raman Spectra in Femtosecond Laser Inscribed Yb:YVO4 Channel Waveguides - Bao, Yi-Fei; Liu, Tao; Kong, Wei-Jin; Luo, Hao-Qi; Liu, Yong; Liu, Fei-Ran; Cheng, Lin (Frontiers in Physics, 2021)
The femtosecond laser writing with double-line technique was employed to fabricate buried channel waveguides with different widths in Yb:YVO4 crystal. Model profiles of the waveguides were captured using the endface coupling setup at the wavelength of 633 nm under TE and TM polarization. Furthermore, the confocal micro-Raman spectra in bulk and waveguide areas were studied at the wavelength of 633 nm. The enhanced Raman intensity were performed in waveguide areas.